2020
DOI: 10.3949/ccjm.87a.ccc009
|View full text |Cite
|
Sign up to set email alerts
|

Renin-angiotensin system inhibitors in COVID-19

Abstract: The statements and opinions expressed in COVID-19 Curbside Consults are based on experience and the available literature as of the date posted. While we try to regularly update this content, any offered recommendations cannot be substituted for the clinical judgment of clinicians caring for individual patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…There was some controversy regarding the use of ACE1inhibitors (ACE-I) and angiotensin II-receptor blockers (ARBs) in patients with COVID-19 since both are known to increase ACE2 level that is the receptor for SARS-CoV-2 [139]. However, since the primary pathology is due to the loss of ACE2, it stands to reason that ACE-I and ARBs can be helpful [140].…”
Section: Raas Inhibitorsmentioning
confidence: 99%
“…There was some controversy regarding the use of ACE1inhibitors (ACE-I) and angiotensin II-receptor blockers (ARBs) in patients with COVID-19 since both are known to increase ACE2 level that is the receptor for SARS-CoV-2 [139]. However, since the primary pathology is due to the loss of ACE2, it stands to reason that ACE-I and ARBs can be helpful [140].…”
Section: Raas Inhibitorsmentioning
confidence: 99%
“…Because SARS-CoV-2 is found in the urine, kidney damage pattern caused by the virus is limited to areas with ACE2 receptor, and the time course in which the virus appears in the urine coincides with the onset of AKI, so it was suggested that the virus directly affects the kidneys [35] , [36] , [37] . The virus is claimed to enter the kidney cell by binding to membrane-bound ACE2 receptors in the glomerular podocyte cells and the apical membrane of proximal tubule cells, and in addition to damaging the kidney epithelial cells, it disarranges the balance of renin-angiotensin system [38] . The angiotensinogen is primarily converted to angiotensin-I by renin and then to angiotensin-II under the influence of angiotensin-converting enzyme (ACE).…”
Section: Epidemiology and Pathophysiology Of Covid-19 Induced Acute Kidney Injurymentioning
confidence: 99%
“…If SARS-CoV-2 occupies ACE2, angiotensin-II levels increase, leading to vasoconstriction, glomerular dysfunction, inflammation, and fibrosis [38] , [39] .Recently Wang et al and Chiu et al found that SARS-CoV-2 also invades host cells via CD 147-spike protein pathway and this glycoprotein is highly expressed in proximal tubule [40] , [41] . Moreover, SARS-CoV-2 causes kidney damage by activating inflammatory pathways and cytokine storm, activating coagulation pathways, damage to renal vascular endothelium, sepsis, hemodynamic instability as well as hypoxemia [38] , [42] , [43] . Viral infection of endothelium via immune cell recruitment causes defective endothelial function and reduces the production of vasodilators, including the nitric oxide.…”
Section: Epidemiology and Pathophysiology Of Covid-19 Induced Acute Kidney Injurymentioning
confidence: 99%
“…These will need individual management since some medications, specifically ACE inhibitors, are associated with a poor response to COVID-19 infection. 1821 It is suggested that Vitamin D supplementation may be a prophylactic measure, particularly for BAME personnel, but this remains unproven. We would also suggest that even non-diabetic staff with the Metabolic Syndrome be offered treatment with Metformin.…”
Section: Uk Experiencementioning
confidence: 99%